Relationship between Head of Room Leadership Style and Level of Job Satisfaction of Nurses in Inpatient Room of Tajuddin chalid Hospital - Syahrir, Syahrir; Fatmawati, Fatmawati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Career is all work that exists as long as a person works or it can also be said that a career is all positions occupied or all levels of education followed in the work life of a person. This research uses an analytic survey using a cross-sectional study approach, where the aim is to identify related to efforts to develop a nurse's career. This research was conducted at Dr. Hospital. Tadjuddin Chalid Makassar. The sample size in this study was 40 respondents who fit the inclusion criteria. Data collection was carried out by observing and distributing questionnaires to respondents, where to see factors related to efforts to develop a nurse's career. In this study, the chi-square test was used with the correction of the Fisher exact test at a significance level of a= 0.05. Based on the research results, it was found that there was a relationship between education and efforts to develop a nurse's career (p=0.000), there was a relationship between tenure and efforts to develop a nurse's career (p=0.027). Also, there was a relationship between motivation and efforts to develop a nurse's career (p=0.004). The conclusion in this study is that there is a relationship between education, years of service, and motivation on career development efforts. The suggestions in this study are expected to be useful for the community as reading material and also as reference material for people who want to know more about the development of the nursing profession. Based on the research results, it was found that there was a relationship between education and efforts to develop a nurse's career (p=0.000), there was a relationship between tenure and efforts to develop a nurse's career (p=0.027). Also, there was a relationship between motivation and efforts to develop a nurse's career (p=0.004). The conclusion in this study is that there is a relationship between education, years of service, and motivation on career development efforts. The suggestions in this study are expected to be useful for the community as reading material and also as reference material for people who want to know more about the development of the nursing profession. Based on the research results, it was found that there was a relationship between education and efforts to develop a nurse's career (p=0.000), there was a relationship between tenure and efforts to develop a nurse's career (p=0.027). Also, there was a relationship between motivation and efforts to develop a nurse's career (p=0.004). The conclusion in this study is that there is a relationship between education, years of service, and motivation on career development efforts. The suggestions in this study are expected to be useful for the community as reading material and also as reference material for people who want to know more about the development of the nursing profession. The conclusion in this study is that there is a relationship between education, years of service, and motivation on career development efforts. The suggestions in this study are expected to be useful for the community as reading material and also as reference material for people who want to know more about the development of the nursing profession. The conclusion in this study is that there is a relationship between education, years of service, and motivation on career development efforts. The suggestions in this study are expected to be useful for the community as reading material and also as reference material for people who want to know more about the development of the nursing profession.